Being Genderless of Public Sphere and Sport - Murat Yüksel (Türk Spor ve Egzersiz Dergisi)
The public sphere is a common living sphere open to the participation of individuals. It is seen that the public sphere where each individual is involved with different purposes and can express his ideas freely is rapidly becoming genderless in modern societies. The aim of this study is to reveal how being genderless of public sphere is reflected in the sporting area, which is one of the social institutions. The research carried out in Istanbul and was applied to a total of 1000 people, 526 of them are women and 474 of them are men, by random sampling technique. According to findings of the research, it was found a high significant relationship between gender and “It is not right that women and men do sports with together” and “Adult girls and women should not do sports”. Those who answered the question as "I do not agree" was 59% of women and 69% of men. In the second question, the rate of those who do not agree with the opinion that women should not do sports is 95% for women and 91% for men. According to this, it is seen that a transformation was created from a structure that women were not seen proper to do sports to a structure that both women and men do sports and both women and men included in some sports that they took place together. As a result, it is seen that the public sphere has also become significantly genderless.